Inculcating the Essence of ‘Wasatiyyah’ in Muslim Society: The State Promotion and Muslim Intelligentsia Responses in Malaysia - Mohammad Redzuan Othman; Mashitah Sulaiman (International Institute of Islamic Thought and Civilisation(ISTAC), International Islamic University Malaysia (IIUM), 2024)
VOL. 19 NO. 2